SPONTANEOUS THIRD-DEGREE ATRIOVENTRICULAR BLOCK IN A DIABETIC PATIENT PRESENTING AS RECURRENT SYNCOPE - Raina, Rohit; Jain, Vikram; S, Srikant; Agarwal, Mayank; Kant, Ravi (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Chronic, uncontrolled hyperglycemia is associated with an increased incidence of coronary artery disease, cardiac failure, diabetic nephropathy, diabetic retinopathy, and associated mortality. A 72-year-old female presented to the OPD with multiple episodes of loss of consciousness for the past 1 month. The patient also had other comorbidities such as hypertension, diabetes mellitus (DM), and hypothyroidism. On systemic examination, her blood pressure was 124/77 mmHg (supine) and 116/72 mmHg (standing), and her pulse rate was 56 beats/min. She had a loss of vibration sense in both lower limbs up to the ankle. Fundus examination showed non-proliferative diabetic retinopathy. The rest of the systemic examination was clinically normal. Her HbA1C was 8.1%, and other routine investigations were within normal limits. Electrocardiography (ECG) showed sinus bradycardia. Echocardiography showed normal ventricular function with no evidence of ischemic heart disease (IHD). 24-h Holter ECG revealed sinus bradycardia with an intraventricular conduction defect, a third-degree AV block with junctional beats, and rare supraventricular ectopics. This is a case of Type 2 DM with complete heart block (CHB) of spontaneous onset. Other causes of AV block have been ruled out, and it seems that this case of CHB is possibly due to cardiac autonomic neuropathy (CAN). Multiple factors, such as the duration of diabetes, poor glycemic control, metabolic derangements, and genetic factors, determine CAN. This case emphasizes that patients with type 2 diabetes without IHD can develop CHB spontaneously.